2013
DOI: 10.1186/1471-2105-14-333
|View full text |Cite
|
Sign up to set email alerts
|

Similarity maps and hierarchical clustering for annotating FT-IR spectral images

Abstract: BackgroundUnsupervised segmentation of multi-spectral images plays an important role in annotating infrared microscopic images and is an essential step in label-free spectral histopathology. In this context, diverse clustering approaches have been utilized and evaluated in order to achieve segmentations of Fourier Transform Infrared (FT-IR) microscopic images that agree with histopathological characterization.ResultsWe introduce so-called interactive similarity maps as an alternative annotation strategy for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Conventionally, the dendrogram of hierarchically clustered image spectra is cut "horizontally" to obtain a segmentation into a fixed number of clusters. In Zhong et al 38 however, it has been shown by one of the authors that cutting dendrograms through "non horizontal" cuts yields biologically more meaningful segmentations for IR image spectra. As our newly contributed colocalization scheme generally also identifies such non-horizontal cuts, the present study supports this claim also for Raman spectral image segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, the dendrogram of hierarchically clustered image spectra is cut "horizontally" to obtain a segmentation into a fixed number of clusters. In Zhong et al 38 however, it has been shown by one of the authors that cutting dendrograms through "non horizontal" cuts yields biologically more meaningful segmentations for IR image spectra. As our newly contributed colocalization scheme generally also identifies such non-horizontal cuts, the present study supports this claim also for Raman spectral image segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, multivariate methods were applied to the analysis of imaging data sets. [17][18][19] In one of these methods (known as unsupervised hierarchical cluster analysis [HCA]) 20 the entire spectrum is used, and a correlation of each spectrum with all other spectra in the data set is performed. Subsequently, the values of the correlation coefficients may be displayed at the pixel coordinates, again as grayscale or pseudocolor images, to reveal similarity of the pixel spectra.…”
Section: Spectral Histopathologymentioning
confidence: 99%
“…On the other hand, it is well-established that clustering unveils tissue structure in FTIR, Raman and CARS images relatively well in general, and is in fact commonly used for spectral image segmentation. While supervised or interactive [ 21 , 22 ] approaches are known to achieve segmentations that display biologically relevant structures more accurately, such approaches require either prior knowledge or manual interactions, contradicting our goal of achieving a fully unsupervised registration. It is also known that hierarchical clustering represents tissue structure better than non-hierarchical approaches [ 21 ], but at the cost of significantly higher demands in running time and memory.…”
Section: Introductionmentioning
confidence: 99%